RISING DRUG ABUSE AMONG ADOLESCENTS AND ITS IMPACT ON EDUCATIONAL ACHIEVEMENT: A SOCIOLOGICAL STUDY OF THE JAIPUR URBAN AREA - Saini, Kalpana; Joshi, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Drugs are chemical substances that affect adolescents’ actions, processes, and learning. The term drug abuse has been used to describe a situation that may involve repeated physical danger, social or interpersonal problems, or legal problems. From a sociological perspective, habit formation is defined as